Application Of Wazuh To Conduct Monitoring Network Security System (Case Study Of SMK N 1 Bengkulu City) - Aripilahi, Edwin; Khairil, Khairil; Akbar, Abdussalam Al (Fakultas Ilmu Komputer Universitas Dehasen Bengkulu, 2024)
The application of Wazuh to monitor network security systems at SMK Negeri 1 Bengkulu City can help network operators monitor security systems, computers and make it easier to control the devices being monitored, so that they can take action as soon as possible if there is a disruption to the system and network based on the monitoring results. Wazuh can monitor files in the directory folder. The information provided is in the form of adding, modifying and deleting files contained in the directory folder. Based on the tests carried out, the results showed that the application of Wazuh to monitor the network security system at SMK Negeri 1 Bengkulu City was running well and could help network administrators by providing information related to the agent device being monitored.